Equity research : Mercedes-Benz Group AG - Carvalho, António Jorge Magalhães Paes de (2024)
The following equity research on Mercedes-Benz Group AG represents my Master’s Final Work in respect to the Master’s Degree in Finance of ISEG – Lisbon School of Economics and Management. The objective of this project is to provide a recommendation of Mercedes-Benz Group Stock, following the CFA Institute recommendations. Mercedes-Benz is a leading automotive company headquartered in Stuttgart, Germany, that offers premium and luxury vehicles and a collection of multi-purpose vans, alongside several financial services related with automotive insurance, leasing packages and fleet management. The Group is determined to keep its position as a world leader in the production of exciting high-quality vehicles, while focusing on innovative technological progress, safety, comfort and sustainability. We issue a BUY recommendation for Mercedes-Benz Group AG (MBG.DE) with a price target of €67.09/share for 2025YE, using the WACC method, with an upside potential of 15.59% against the closing price of €58.04 of September 30th, 2024, with medium risk. Additional valuation methods were used to complement the valuation (Flow to Equity, Adjusted Present Value, Dividend Discount Method), as well as a relative valuation based on Enterprise Value and Price Multiples. The designated peers were selected using the Sum of Absolute Differences (SARD) methodology and comprise of Volkswagen AG, Toyota Motor Corporation, Bayerische Motoren Werke AG and Hyundai Motor Company.